Comment on 'Estimating a modified Grubb's exponent in healthy human brains with near infrared spectroscopy and transcranial Doppler'. - Boas, D; Payne, S (2009)
The relationship between cerebral blood volume (CBV) and blood flow (CBF) has gained widespread interest because of its utility in using functional magnetic resonance imaging and optical imaging methods to estimate the cerebral metabolic rate of oxygen (CMRO(2)). A recent paper by Leung et al (2009 Physiol. Meas. 30 1-12) nicely presents measurements relating CBV to cerebral blood flow velocity (CBFV) as measured by near infrared spectroscopy and transcranial Doppler, respectively. They suggest that this relationship cannot be inverted to estimate CBF (or CBFV) from CBV, and that doing so to estimate CMRO(2) is inappropriate. We argue that these data, and other related published data, do permit the estimation of CBF from CBV and thus enable CMRO(2) to be estimated when only measures of CBV and deoxygenated hemoglobin are available.